Analysis of cervical cytology in tertiary care hospital - Khan, Samira Shafi (Grande Medical Journal, 2024)
Background Cancer of the cervix is the third most common cancer in women. In Nepal and other developing countries cervical cancer is the leading cause of morbidity and mortality. Cancer of cervix is readily preventable, and can be diagnosed at the pre-invasive stage with cytological screening with Papanicolaou (Pap) smears.Method This is a retrospective study aimed to evaluate all previously conducted cervical smears examined at Grande International hospital during a one-year period. Pap smear cytology reports were obtained and data noted in a structured Performa. All the smears were reported as per the 2001 Bethesda system.Result A total of 3202 Pap smears were examined. Maximum number of patients was in the age group of 36 to 50 years. A total of 3161 smears were reported as Negative for Intraepithelial Lesion or Malignancy (NILM), of which 2944 showed normal cytological findings and 217 were inflammatory. The abnormal cases comprised of two cases with ASC-US, 33 cases of LSIL, 4 cases of HSIL, and 2 cases of invasive Squamous cell carcinoma.Conclusion Premalignant and malignant lesions of cervix can be diagnosed easily by Pap smears.